2005
DOI: 10.1021/es040534q
|View full text |Cite
|
Sign up to set email alerts
|

Simulated Inhalation Levels of Fragrance Materials in a Surrogate Air Freshener Formulation

Abstract: This study measured postapplication exposure levels of fragrance materials in a surrogate air freshener formulation in an environmentally-controlled exposure room (ECER). A five-s spray was released to simulate normal consumer use conditions. Time-course airborne fragrance material levels were sampled with Tenax tubes, and aerosol size distributions were monitored with a TSI 3320 aerodynamic particle sizer. Triplicate experiments were performed for each of the control/test substances. The control substance (un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(14 citation statements)
references
References 12 publications
(12 reference statements)
1
13
0
Order By: Relevance
“…Aerosols produced from consumer sprays have been analyzed in the micrometer range by Rogers et al (2005) and Vernez et al (2006). For waterproofing sprays, Yamashita and coworkers reported that in the micrometer range the particle diameter is related to the toxicity of the spray products (Yamashita et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Aerosols produced from consumer sprays have been analyzed in the micrometer range by Rogers et al (2005) and Vernez et al (2006). For waterproofing sprays, Yamashita and coworkers reported that in the micrometer range the particle diameter is related to the toxicity of the spray products (Yamashita et al 1997).…”
Section: Introductionmentioning
confidence: 99%
“…After completing the clinical review, subjects were exposed to either the TS or CS for 15 or 30 min in an environmentally controlled exposure chamber (9.1 m 3 ) with an air exchange rate of 0.6/h (AE0.1), previously established to simulate typical residential ventilation [23]. This incorporated a standardized product instilled through a spray canister (two sprays per exposure) with measurement of background levels of the substances captured using absorbent tubes with carbon capture (Dr CJC; Toxcon, Edmonton, Alberta, Canada).…”
Section: Exposure Protocolmentioning
confidence: 99%
“…The CS aerosol preparation was identical to the TS except the fragrance materials were replaced with deionized distilled water. Double distilled water made up the percentage in the placebo of what was the fragrance formulation in the test aerosol [23].…”
Section: Exposure Protocolmentioning
confidence: 99%
“…7 Therefore, if they are not metabolised, they have the potential to be accumulated from water and/or diet by aquatic organisms. [8][9][10][11][12][13] Fragrance ingredients are subject to regulation under REACH, which requires evaluation of their potential for bioaccumulation using a metric like the bioconcentration factor (BCF).…”
Section: Introductionmentioning
confidence: 99%